Design for additive manufacturing of porous structures using stochastic point-cloud: a pragmatic approach. Issue 1 (2nd January 2018) - Sharif Ullah, AMM
ABSTRACT: In this article, we address the design for additive manufacturing of porous structures. As a means, we employ Monte Carlo simulation (i.e., stochastic processes) to create a set of layered point-clouds so that the solid models generated from the point-clouds exhibit randomly distributed porous structures. Finally, we build physical models from the solid models using the commercially available additive manufacturing facilities (e.g., 3D Printer). The outcomes of this study will benefit those who need to manufacture the shapes found in nature (fractals) and biological organisms (e.g., artificial tissues) in a more sustainable way. GRAPHICAL ABSTRACT: